Decompressive craniotomy for the treatment of malignant infarction of the middle cerebral artery: mortality and outcome - Gianise Toboliski Bongiorni; Marjeane Cristina Jaques Hockmuller; Cristini Klein; Ápio Cláudio Martins Antunes (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective To assess, by Rankin scale, the functional disability of patients who had a malignant middle cerebral artery (MCA) ischemic stroke, who underwent decompressive craniotomy (DC) within the first 30 days. Methods A cross-sectional study in a University hospital. Between June 2007 and December 2014, we retrospectively analyzed the records of all patients submitted to DC due to a malignant MCA infarction. The mortality rate was defined during the hospitalization period. The modified outcome Rankin score (mRS) was measured 30 days after the procedure, for stratification of the quality of life. Results The DC mortality rate was 30% (95% CI 14.5 to 51.9) for the 20 patients reported. The mRS 30 days postoperatively was ≥ 4 [3.3 to 6] for all patients thereafter. Conclusion DC is to be considered a real alternative for the treatment of patients with a malignant ischemic MCA infarction.